2018
DOI: 10.1080/16512235.2018.1548250
|View full text |Cite
|
Sign up to set email alerts
|

Gut thinking: the gut microbiome and mental health beyond the head

Abstract: Background: In recent decades, dominant models of mental illness have become increasingly focused on the head, with mental disorders being figured as brain disorders. However, research into the active role that the microbiome-gut-brain axis plays in affecting mood and behaviour may lead to the conclusion that mental health is more than an internalised problem of individual brains.Objective: This article explores the implications of shifting understandings about mental health that have come about through resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…The role of the gut microbiome for mental and physical health disorders received increasing research interest in recent years [ 84 , 85 ]. A study conducted in rats investigated the effect of sleep fragmentation on their gut microbiome and fecal metabolome [ 82 ].…”
Section: Sleep Fragmentationmentioning
confidence: 99%
“…The role of the gut microbiome for mental and physical health disorders received increasing research interest in recent years [ 84 , 85 ]. A study conducted in rats investigated the effect of sleep fragmentation on their gut microbiome and fecal metabolome [ 82 ].…”
Section: Sleep Fragmentationmentioning
confidence: 99%
“…Restoring a balanced gut microbiota is considered as a therapeutic tool for various diseases, including OP [ 695 , 730 , 731 , 732 , 733 , 734 , 735 , 736 , 737 ]. Recent studies showed that probiotic and prebiotic supplementation increases bone density in healthy individuals, protects against primary and secondary OP [ 687 , 695 , 699 , 734 , 738 , 739 , 740 ] and exerts beneficial effects in many other extra-digestive diseases [ 740 ]. However, despite the established impact of the gut microbiota on host (patho-) physiology, the potential roles of HPI- and medications-induced gut dysbiosis is not mentioned in current guidelines for OP.…”
Section: Clinical Implications and Recommendationsmentioning
confidence: 99%
“…Similarly, there is debate about the various methods used to measure mood (62,63). It is acknowledged that from both a physiological and cognitive standpoint that accurately and consistently capturing valid and reliable data can be biased toward emotionally salient information that reflects one's emotional state at that present moment (61).…”
Section: Discussionmentioning
confidence: 99%